PEMANFAATAN QUALITY COST REPORT PADA QUALITY IMPROVEMENT PROGRAM DALAM RANGKA EFISIENSI BIAYA PRODUKSI PADA PERUSAHAAN - Solikhah Wiratna (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The data analysis technique that used is the ratio of the percentage of the quality cost to the total sales so that it can be known the effectiveness of quality improvement program to the increasing of sales volume. The effectiveness of quality improvement program is starting showing the good change that is there are the increasing performances of this program by achieving percentage of the quality cost to the sales